The Relationship Between Menstrual Cycle And Nutritional Status With The Incidence Of Primary Dysminorrhoea In Adolescent Girls In PKLK Junior High School Kaur District - Astuti, Rika Mulya; Rohani, Tuti; Darmawansyah, Darmawansyah (Journal of International Public Health, 2023)
WHO says that 1,769,425 people (90%) of women experience dysmenorrhoea, 10-15% of whom experience severe dysmenorrhoea. Indonesia the incidence of dysmenorrhoea consists of 72.89% primary dysmenorrhoea and among women of productive age consists of 54.89% primary dysmenorrhoea. Data from Puskesmas Bintuhan Kaur Regency shows that primary dysmenorrhoea cases increase every year. The results of the initial survey at SMP PKLK Kaur Regency were conducted on 10 students, obtained 70% of students experiencing primary dysmenorrhoea. The purpose of the study was to determine the relationship between the menstrual cycle and nutritional status with the incidence of primary dysmenorrhoea in adolescent girls at SMP PKLK Kaur Regency. This research is a quantitative research using cross sectional study design. The number of samples in the study were 64 respondents. The analysis used was univariate and bivariate analysis with chi-square test. The results showed that most of the respondents experienced primary dysmenorrhoea by 53.1%, almost half of the respondents experienced an abnormal menstrual cycle by 43.8%, almost half of the respondents experienced abnormal nutritional status by 37.5%. There is a significant relationship between the menstrual cycle and the incidence of primary dysmenorrhoea (p=0.020) and there is no significant relationship between the menstrual cycle and the incidence of primary dysmenorrhoea (P=0.093) in adolescent girls at SMP PKLK Kaur Regency. It is hoped that further research can look at other risk factors using multivariate analysis.